Desafios do atendimento pedagógico hospitalar/domiciliar em Goiás: gênero e docência no olhar dos/as agentes envolvidos/as - Jesus, Edna Maria de (2017)
The research "Pedagogical Hospital / Home Care in Goiás: gender and teaching in the eyes of the subjects involved" had the purpose of investigating the Pedagogical Hospital / Home Care, seeking their particularities in the quality of public policy, as well as the professional identity of the subjects involved in it and the perception of the subjects involved, about the attendance developed by Naeh / Seduce-GO, considering the question of gender and teaching. The research adopts the assumptions of the qualitative approach and is structured by literature review, from a bibliographic study based on authors such as Aranha (2000, 2001, 2005); Ceccim (1999); Fonseca (2003); Freire (1987, 2001, 2006, 2011); Louro (1997, 2003), Matos and Mugiatti (2009, 2014) among others, and documentary and by the articulation of theoretical assumptions with the empirical context, through field research, through questionnaires and interviews. The study revealed that public policies aimed at inclusion, despite advances, were limited in scope and, therefore, the inclusion / exclusion paradox is still evident. In the view of the research subjects, the Pedagogical Hospital / Home Care, offered by Naeh assumes the role of promoter of inclusion and has expanded significantly. However, it is important to highlight some relevant points of the research: a) lack of training to act in this modality of Special Education; b) the plans and activities are elaborated through the Curriculum Reference of the State Education Network - Seduce / GO; c) Pedagogical practice in the Pedagogical Hospital / Home Care requires the professionals involved / the greater flexibility, greater understanding of the peculiarities of each student; d) the difficulty of the professionals who work in this modality of teaching, in dealing with the loss and mourning of learners; e) the turnover of professionals and students that hinders the continuity of the teaching / learning process; f) most professionals, from Naeh, have an effective link in Seduce-GO, but they are crowded in other educational institutions and only complement the workload in this kind of service; g) although there is no resistance regarding the hiring of teachers and preference for the hiring of teachers, most of the professionals who work in the Pedagogical Hospital / Home Care, in the management and teaching positions, are women; h) those responsible are all female and do not perform paid work outside the home to accompany the child in health treatment; i) the majority of those interviewed declare that they prefer teachers because of the issue of caring and educating, recognized by them, as a feminine activity; j) those responsible state that they learned about the Pediatric Hospital / Home Care at the hospital during the hospitalization of the child and consider the activities of relevance to the beginning or continuity of school activities, as well as social interrelations. In this way, the elements constituting the look of pedagogical work were presented and analyzed, in the Pedagogical Hospital / Home Care Service in Goiás, which still has a long way to go in order to achieve inclusion and equal rights.